THE DESCRIPTION OF MUNKER HADITH ACCORDING TO MUTAQADDIMIN AND MUTAAKHIRIN HADITH SCIENTIST - Muhammed Aslan (Fırat University, 2019)
The hadith method, practiced since the exilic first century and recorded since the late second century, assesses and limits the rules and methods related to the documents and texts in hadiths, the qualifications of the deferent and the hadith concepts. One of the important concepts that is evaluated and limited in the hadith methodology is the concept of the münker hadith. In the dictionary, the notion of "münker" is described as "ugly, evil, unreasonable, denied, or every act that the authentic mind considers bad", and defined in several ways related to the hadith. Also, like the Qur'an and the hadith, it has been used several times in the basic Islamic sources, obtaining a religious meaning close to its lexical meaning. Münker hadith that has direct or indirect associations with other hadith types such as the known (ma’ruf) hadith, şaz hadith, muallel hadith and garip hadith has been used since the late second century. The meaning of the term munker hadith had a tendency of expansion and sometimes narrowing in time and it is the most defined type of hadith. The oldest known definition was found in Yahya b. Said al-Kattan (dated 198/813) and was finalized by Ibn Hajjar (d. 852/1449) as "the münker hadith is the hadith that was related by the weak deferent as opposed to the just deferent." During the seven centuries between the exilic second and ninth centuries, münker hadith was used in at least seven meanings as far as we could establish.